Numérique et humanités : de l’ancillarité à la fécondité grâce à la modélisation computationnelle des connaissances - Yannis Delmas-Rigoutsos (Humanités Numériques)
The digital transformation of society also affects the humanities and social sciences (HSS). The digital humanities follow the general pattern of digital history, which we will briefly describe. A first period limits digital technology to large projects or organisations, mainly for statistical processing. From the mid-1970s to the early 2000s, the personal computer and common IT software induce a first phase of growth in the digital humanities: databases, digitisation of texts and publishing tools. Since the end of the 1990s, new tools have been developed for collecting, organising and accessing digital content, including the considerable volume of big data. We plead here for an amplification of the relationship between HSS and computer science, exploiting not only technologies, but also ideas and methods, especially computational thinking. To illustrate this point, we present some examples of computational analysis in the field of history.